COMPENSATORY GROWTH OF Oreochromis niloticus SELECTED STRAIN FROM BOGOR, WEST JAVA - Vitas Atmadi Prakoso; Kurniawan Kurniawan (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2017)
Inefficient feed management strategy in aquaculture will increase the fish production cost. One of the most effective strategies to solve this problem is through a better understanding of the compensatory growth of cultured fish. O. niloticus BEST tilapia strain (total length: 7.23 ± 0.11 cm mean ± SD; Body weight: 7.04 ± 0.08 g mean ± SD) were reared in aquariums at 26.3 ± 1.4oC for 10 weeks. During the experiment, the control group was fed twice a day. The other two groups were deprived of food for one and two weeks and then fed twice a day during refeeding period. At the end of the experiment, the fish deprived for one week had a body weight, biomass and specific growth rate that were not significantly different from the control group. The body weight, biomass and specific growth rate of fish deprived for two weeks were significantly lower than the other groups. This study revealed that concentrations of ash and lower concentrations of protein and lipid on the deprived groups were higher compared to those without feed deprivation. Mortality of fish was lower than 9% and not significantly different among the treatments. Fish aggressive behavior was the main reason for injuries and death. Given the results, BEST tilapia strain was only able to reach complete growth compensation not longer than one week deprivation period. The results of the present study could be applied as basic information for further research on feeding management of BEST tilapia strain.